OPTIMALISASI PENGELOLAAN OBJEK DANAU KEPUNGO DALAM MENINGKATKAN PENDAPATAN ASLI DESA BALAI RAJO KECAMATAN VII KOTO ILIR KABUPATEN TEBO TAHUN 2020 - Joko Setyoko; Ahmad Riyadi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
This study aims to determine how the performance of the Hamlet Government apparatus in serving and building the economy through an optimization process. the people of Balai Rajo Hamlet, VII Koto Ilir District, Tebo Regency, Furthermore, what affects the performance of the Hamlet Government apparatus in serving and building the village economy and the community in realizing a safe and prosperous independent village for the people of Balai Rajo Hamlet, VII Koto Ilir District, Tebo Regency. The ability of human resources (HR) is a factor that affects the performance of the apparatus. The problem of the quality of human resources of the Dusun government is an important issue in the implementation of Autoda. Therefore, increasing the Human Resources (HR) of the Dusun government is an urgent matter that must be done, so that the implementation of Autoda can run as expected, but this is also influenced by two important factors. Level of education In carrying out its duties and responsibilities as a Dusun apparatus, especially in providing services and development of general village economic growth to Balai Rajo Hamlet, it is largely determined by the level of education possessed by the apparatus itself, because the heavier or wider the responsibility of the Dusun apparatus must be carried out. It takes an apparatus that has quality human resources as well. Work experience In carrying out their duties and responsibilities as community servants, the ability of the apparatus is also greatly influenced by the length of work or in terms of work experience, therefore the village government, which has been working for a long time, is demanded to be more effective and recognize what can give satisfaction to visitors and visitors. community Service facilities and infrastructure are all types of equipment, work equipment, and other facilities that function as the main or auxiliary tools in the implementation of work. The role of service facilities is very important in addition to the role of the human element itself. One that is also very influential on improving the quality of work is the spirit and commitment to work that leads to a better direction than the previous results.